Analisis Tingkat Kompetensi Guru Sekolah Dasar Guna Mewujudkan Profesional dalam Pembelajaran - Rahma Annisa; Rizqa Ni'matul Abrar; Winda Nur Febrianti; Vina Nur Hidayah; Istiningsih (Jurnal Sekolah Dasar, 2023)
The purpose of this study is to find out how the level of professional ability of elementary school teachers, especially in pedagogic, interpersonal, communication and information technology competencies in the province of D.I. Yogyakarta. The research method used is descriptive quantitative method. The subjects of this research are elementary school teachers in Yogyakarta. The number of teachers who became the subject was 16 teachers from the primary school level, both public and private, in the province of Yogyakarta. The collection of research data was obtained through a closed questionnaire with a Google Form Linkert scale. The results of the study indicate that the average percentage of the overall professional competence of teachers in the realm of interpersonal, communication, information technology and pedagogy competencies, the overall average is 95% appropriate and valid. Based on this, it can be concluded that the competencies possessed by new and old teachers are in accordance with professional competency standards that have been established through indicators set by researchers.